2009
DOI: 10.1037/a0016273
|View full text |Cite
|
Sign up to set email alerts
|

Use of self-to-object and object-to-object spatial relations in locomotion.

Abstract: Eight experiments examined the use of representations of self-to-object or object-to-object spatial relations during locomotion. Participants learned geometrically regular or irregular layouts of objects while standing at the edge or in the middle, and then pointed to objects while blindfolded in three conditions: before turning (baseline), after rotating 240 degrees (updating), and after disorientation (disorientation). The internal consistency of pointing in the disorientation condition was equivalent to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 20 publications
3
34
1
Order By: Relevance
“…This is also consistent with Xiao, Mou and McNamara, (2009), who 29 suggested that allocentric frames of reference are more likely to be employed in a regular array, such as the one used in the current experiment (9 distinct locations along the horizontal axis, flanked by one or two anchors).…”
Section: Discussionsupporting
confidence: 78%
“…This is also consistent with Xiao, Mou and McNamara, (2009), who 29 suggested that allocentric frames of reference are more likely to be employed in a regular array, such as the one used in the current experiment (9 distinct locations along the horizontal axis, flanked by one or two anchors).…”
Section: Discussionsupporting
confidence: 78%
“…For example, Wang and Spelke (2000;Sargent, Dopkins, Philbeck, & Chichka, 2010;Waller & Hodgson, 2006;Xiao, Mou & McNamara, 2009) asked people to learn multiple target objects in a room. They then pointed to these targets before and after disorientation.…”
Section: Some Experimental Evidence the Dynamic Representation Of Mulmentioning
confidence: 99%
“…In particular, object-to-object relational knowledge seems to be highly sensitive to learning conditions (Mou et al, 2006;Waller & Hodgson, 2006;Xiao et al, 2009). In contrast, rooms can be irregularly shaped and viewed piecemeal and still be represented in a way that is robust to disorientation (Wang & Spelke, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We also manipulated learning heading to examine its influence. Learning viewpoint has been shown to affect the selection of reference axes in memory (e.g., McNamara, Rump, & Werner, 2003;Shelton & McNamara, 2001), especially for irregular layouts of objects (Xiao et al, 2009). Other modifications in Experiment 2 were the following: We misaligned the configurations so that participants could not use their knowledge about one configuration to respond on trials for the other; we blocked the four trial types in order to maximize possible differences between them; finally, we reexamined the cost of switching between configurations with a sufficient sample size of 40 participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation